Spinal neural tube formation and tail development in human embryos - Chloe Santos; Abigail R Marshall; Ailish Murray; Kate Metcalfe; Priyanka Narayan; Sandra CP de Castro; Eirini Maniou; Nicholas DE Greene; Gabriel L Galea; Andrew J Copp (eLife, 2024)
Primary and secondary neurulation – processes that form the spinal cord – are incompletely understood in humans, largely due to the challenge of accessing neurulation-stage embryos (3–7 weeks post-conception). Here, we describe findings from 108 human embryos, spanning Carnegie stages (CS) 10–18. Primary neurulation is completed at the posterior neuropore with neural plate bending that is similar, but not identical, to the mouse. Secondary neurulation proceeds from CS13 with formation of a single lumen as in mouse, not coalescence of multiple lumens as in chick. There is no evidence of a ‘transition zone’ from primary to secondary neurulation. Secondary neural tube ‘splitting’ occurs in 60% of proximal human tail regions. A somite is formed every 7 hr in human, compared with 2 hr in mice and a 5 hr ‘segmentation clock’ in human organoids. Termination of axial elongation occurs after down-regulation of WNT3A and FGF8 in the CS15 embryonic tailbud, with a ‘burst’ of apoptosis that may remove neuro-mesodermal progenitors. Hence, the main differences between human and mouse/rat spinal neurulation relate to timing. Investigators are now attempting to recapitulate neurulation events in stem cell-derived organoids, and our results provide ‘normative data’ for interpretation of such research findings.